2019
DOI: 10.3390/f10010026
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependence of Urban Forest Vegetation Invasion Level and Alien Species’ Ecological Success

Abstract: Research Highlights: Urban ecosystems are claimed to be more invaded than natural vegetation. Despite numerous studies, the patterns of alien species occurrence in urban forests are rarely linked to invasion ecology hypotheses. Background and Objectives: We assumed that patterns of invasion level (i.e., neophyte richness) and neophyte ecological success (cover) are context-dependent, i.e., depend on the type of vegetation, and that hypotheses connected with empty niche and biotic acceptance will have the stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 95 publications
(153 reference statements)
3
14
1
Order By: Relevance
“…Our results also join an increasing number of studies that found habitat type to be an important predictor of the magnitude of invasions (Chytrý et al, 2008a; Pyšek et al, 2010a; Pyšek & Chytrý, 2014; Dyderski & Jagodziński, 2019). Our study encompassed a smaller set of habitat types than Wagner et al (2017) due to stronger data filtering.…”
Section: Discussionsupporting
confidence: 86%
“…Our results also join an increasing number of studies that found habitat type to be an important predictor of the magnitude of invasions (Chytrý et al, 2008a; Pyšek et al, 2010a; Pyšek & Chytrý, 2014; Dyderski & Jagodziński, 2019). Our study encompassed a smaller set of habitat types than Wagner et al (2017) due to stronger data filtering.…”
Section: Discussionsupporting
confidence: 86%
“…The degree to which alien species are drivers or passengers of change [84] in urban environments likely depends on the characteristics of the dominant species and the particular ecosystem types [85]. Yet there is limited evidence about the role of emerging urban forests in large cities and their domination by native or alien tree species.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the species composition, it can be concluded that the adjacent forest resembles the human-cultivated forest Chelidonio-Robinietum Jurko 1963 s.l. [ 43 , 44 ]). Taking into account the relatively small distance from the adjacent forest to the territory of the mine including the sandy habitats, the transport of seeds by the wind could be efficient enough to disperse this plant.…”
Section: Discussionmentioning
confidence: 99%